Segregation and Integration: A Study of the Behaviors of Investors with Extended Value Functions. (12th July 2010) - Egozcue, Martin; Wong, Wing-Keung
Abstract : This paper extends prospect theory, mental accounting, and the hedonic editing model by developing an analytical theory to explain the behavior of investors with extended value functions in segregating or integrating multiple outcomes when evaluating mental accounting.